Reevaluation of some of the kinetics of carbon colloid clearance by the mononuclear phagocyte system in vivo. - Al Tuwaijri, A. (1986)
The kinetics of clearance of carbon colloid from the blood stream by the mononuclear phagocyte system in rats and mice was investigated. Results are presented which show that the clearance of blood borne carbon follows non-monoexponential and not monoexponential kinetics as had been thought for the past three decades. Further, it is also shown that the phagocytic index is not dependent upon the dose of carbon injected intravenously.